Can simulation-based education or other education interventions replace clinical placement in medical radiation sciences? A narrative review. Issue 2 (March 2023) - Jimenez, Y.A.; Gray, F.; Di Michele, L.; Said, S.; Reed, W.; Kench, P.
Abstract: Objectives: In response to increasing student enrolment and workload pressures from the Covid-19 pandemic, a recent focus on health student preparation programs has been on curricula adaptations and replacement of clinical placement time with alternative education activities. The aim of the narrative review was to explore the current evidence relating to education activities in Medical Radiation Sciences (MRS) used to replace clinical placements or part of clinical placements. Medline, CINAHL and Web of Science databases were used to search for articles published between 2017 and 2022. Data from the literature was summarised into (1) planning and development of clinical replacement learning activities in MRS, (2) evaluation of clinical replacement activities, and (3) benefits and challenges of clinical replacement in MRS. Key findings: Planning and development of clinical replacement learning activities in MRSrequires support from a wide range of stakeholders, and evidence from activities already implemented exists. Activities largely encompass an institution-specific focus. Developed clinical replacement activities use a blended approach, with simulation-based education (SBE) as a main teaching platform. Evaluation of clinical replacement activities are largely focused on students' achievement of learning objectives relating to practical and communication skills. Emerging evidence based on small student samples shows that clinical and clinical replacement activities provide similar results in terms of learning objectives. Conclusion: Benefits and challenges of clinical replacement in MRS are similar to those presented in the other health professions. The balance between quality and quantity of teaching and learning experiences for clinical skill development in MRS needs to be further investigated. Implications for practice: To meet the dynamic challenges of the health care environment and MRS profession, a major goal in the future will be to affirm the benefit of clinical replacement activities for MRS students.